Manajemen Pembimbing Praktek Kerja Lapangan (PKL) dalam Meningkatkan Disiplin Kerja Siswa SMK Negeri 2 Luwu Utara - Musdalipa Musdalipa (P3I Luwu Raya, 2022)
This research discusses the management of the field work practice supervisor in improving the discipline in working of students at SMK Negeri 2 Luwu Utara. This study aimed at: 1) finding out how is the discipline in working of students at SMK Negeri 2 Luwu Utara who follow Field Work Practices (FWP); 2) To find out the management of Field Work Practice Supervisors in improving of discipline in working of SMK Negeri 2 Luwu Utara students who follow Field Work Practices (PKL); 3) To find out the obstacles faced by the Field Work Practices Supervisor (FWP) in improving the discipline in working of students at SMK Negeri 2 Luwu Utara who take part in Field Work Practices (FWP); and 4) To find out solutions to improve the discipline in working of SMK Negeri 2 Luwu Utara students who follow Field Work Practices (FWP). The type of research was qualitative research with a descriptive approach. The subject of this research was the supervisor of the Field Work Practices (FWP) of SMK Negeri 2 Luwu Utara. Students with total number was 8. Data were obtained by observing, interviewing and documenting. The results showed that: 1) The Discipline of SMK Negeri 2 Luwu Utara students implementing Field Work Practices (FWP) was in good condition. This was supported by the evident that the less of breaking the rules students during the Field Work Practices (FWP). But in this case, the discipline enforcement of North Luwu State Vocational School 2 students who carry out Field Work Practices (FWP) must still be increased and it is needed to be given more intensive attention to the students in the implementation of the discipline; 2) Management of Field Work Practices (FWP) in improving the discipline in working of students at SMK Negeri 2 Luwu Utara who took part in Field Work Practices (FWP) was carried out through three stages, namely: a) planning consisting of activities for the formulation of student disciplinary regulations during the Field Work Practices (FWP) and the stipulation of student discipline rules during Field Work Practices (FWP), b) implementation consisting of activities providing direction regarding discipline in improving student discipline, providing motivation to students in relation to discipline in improving student discipline and provide a decision to impose sanctions for student disciplinary violations and c) supervision which consists of direct and indirect supervision; 3) Obstacles faced by the Field Work Practice Supervisor in improving the discipline in working of students of SMK Negeri 2 Luwu Utara who take part in the Field Working Practices (FWP) include internal factors originating from students, namely the nature and character of students and external factors, namely those that come from outside of the student, such as the environment; and 4) Solutions to improve the work discipline of students of SMK Negeri 2 Luwu Utara who take part in Field Work Practices (FWP) by providing examples, motivating them in implementing discipline and providing sanctions for violations committed.